Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/imds-10-2019-0554
|View full text |Cite
|
Sign up to set email alerts
|

The effect of information technology assimilation on firm performance in B2B scenarios

Abstract: PurposeThe spread of the Internet in the business world has led to the development of new business-to-business (B2B) settings. Although a large number of companies have adopted B2B strategies, many of these fail to implement such strategies effectively. The most common barriers encompass the technology assimilation by users. This study investigates how IT assimilation can encourage potential and realised absorptive capacity and how these can, in turn, facilitate organisational agility and performance.Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 126 publications
0
21
0
Order By: Relevance
“…The special issue also includes articles applying advanced PLS methods in various empirical contexts. Martínez-Caro et al (2021) study how IT assimilation affects performance in the business-to-business (B2B) context, and aim to resolve the debate in the current literature on the direct relationship between IT and firm performance. Drawing on the organization capability view, a complex path model has been developed which proposes that the relationship between IT assimilation and organizational performance is mediated by absorptive capacity (both realized and potential) and organizational agility.…”
Section: Summary Of Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The special issue also includes articles applying advanced PLS methods in various empirical contexts. Martínez-Caro et al (2021) study how IT assimilation affects performance in the business-to-business (B2B) context, and aim to resolve the debate in the current literature on the direct relationship between IT and firm performance. Drawing on the organization capability view, a complex path model has been developed which proposes that the relationship between IT assimilation and organizational performance is mediated by absorptive capacity (both realized and potential) and organizational agility.…”
Section: Summary Of Articlesmentioning
confidence: 99%
“…However, there are many open-ended ways in which PLSpredict can be applied and it has taken some time for the PLS community to formalize best practices that are compatible with existing research approaches. The article by Martínez-Caro et al (2021) in this issue demonstrates one straightforward way in which researchers have interpreted PLSpredict, while Chin et al (2021) examine wider causal-prediction criteria. Researchers would benefit from applying these methods to future-proof their research by ensuring its validity in other samples or future data.…”
Section: Future Directionsmentioning
confidence: 99%
“…an expert with specialised knowledge), the growing role of its capabilities, as well as intangible assets, have been given more attention (Liang et al , 2010; Lioukas et al , 2016; Wade and Hulland, 2004). Third, previous studies have demonstrated that information strategy can facilitate innovation and superior performance through improved efficiency and effectiveness, and reduced uncertainty (Martínez-Caro et al , 2020; Prince et al , 2019).…”
Section: Introductionmentioning
confidence: 98%
“…A firm’s information strategy is a plan, implementation and management of a strategy utilising valuable resource of information, knowledge or data to accomplish its objectives (Lioukas et al , 2016; Markovich et al , 2019; Martínez-Caro et al , 2020; Smits and van der Poel, 1996; Wade and Hulland, 2004). It is therefore a crucial factor for business performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation